Characterization and typification of citrus production systems in the department of meta (2014)
Agriculture is a co-evolutionary process between society and nature. Agroecology is an environmental science which focuses on ecosystem-culture and society-nature interactive systems, the effect of human intervention in the transformation of ecosystems. The central objects are agroecosystems and the units of study are production units. These production units are conceived of as agricultural systems and are found in the crossroads of multiple interactions between biophysical, socioeconomical, cultural, and production components, which must be analyzed with an integrated concept. In the present study, a characterization and typification of the citrus agroecosystems of the department of Meta were pursued (Colombia). The pertinence of implementing the methodology designed by the Latin-American Center for Rural Development (Centro Latinoamericano para el Desarrollo Rural-RI MISP) was evaluated, grouping the variables with a focus on an analysis of livelihoods. A survey and interview were defined as methods of collecting the primary information in the municipalities of Puerto Lopez, Villavicencio, Granada, Lejanias, Guamal and San Martin, where 78.4% of the citrus area of the department is found. This study involved the selection and definition of the evaluation variables, validation and adjustment of said variables, collection of primary and secondary information, and the application of multivariate statistical analysis techniques to conform and characterize the recommendation domains or groups. The more important results indicated that it is possible to increase knowledge of the interrelations that exist between the different components of farm agroecosystems and their relationship with the principal agroecological structure. The existence of six agricultural groups or recommendation domains was established, with some productive characteristics very similar within the group but very heterogeneous to the outside of the group, with particular necessities.